2018 15th Annual IEEE International Conference on Sensing, Communication, and Networking (SECON) 2018
DOI: 10.1109/sahcn.2018.8397129
|View full text |Cite
|
Sign up to set email alerts
|

Fog Following Me: Latency and Quality Balanced Task Allocation in Vehicular Fog Computing

Abstract: Emerging vehicular applications, such as real-time situational awareness and cooperative lane change, demand for sufficient computing resources at the edge to conduct time-critical and data-intensive tasks. This paper proposes Fog Following Me (Folo), a novel solution for latency and quality balanced task allocation in vehicular fog computing. Folo is designed to support the mobility of vehicles, including ones generating tasks and the others serving as fog nodes. We formulate the process of task allocation ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 27 publications
0
56
0
Order By: Relevance
“…According to the responding messages, the client vehicle can choose one fog node for offloading. In this paper, we just adopt a simple fog node selection scheme, in which the client vehicle would select the fog node with the shortest communication distance for task offloading [6], [18].…”
Section: B Process Of Chameleonmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the responding messages, the client vehicle can choose one fog node for offloading. In this paper, we just adopt a simple fog node selection scheme, in which the client vehicle would select the fog node with the shortest communication distance for task offloading [6], [18].…”
Section: B Process Of Chameleonmentioning
confidence: 99%
“…To provide low-latency processing for assisted driving, a novel computing paradigm called vehicular fog computing (VFC) [2]- [6] has been proposed. Its key idea is to offload computational tasks from the client vehicles where data is generated to fog nodes located at for example 5G cell towers or buses with extra computing power.…”
mentioning
confidence: 99%
“…On the other hand, offloading these tasks to the cloud is not applicable, due to the remarkable transmission delay. Thus, the concept of vehicular fog computing has been proposed and widely explored by plenty of works [18], [19], [20], [21], [22]. Xiao et al [19] proposed to turn commercial fleets into fog nodes to serve neighboring vehicles and passengers, while Hou et al [18] suggested utilizing the extra computing power on slow moving or parked vehicles.…”
Section: B Vehicular Fog Computingmentioning
confidence: 99%
“…Furthermore, Zhu et at. [21], [22] designed a system for latency and performance balanced task offloading for video transmission and processing in vehicular networking.…”
Section: B Vehicular Fog Computingmentioning
confidence: 99%
See 1 more Smart Citation